INVESTIGASI DETERMINAN PENCEGAHAN KECURANGAN (FRAUD) DALAM LAYANAN J&T EKSPRESS DI PEKANBARU - Anisa Afmin, Dewi; Marlina, Evi; Samsiah, Siti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This research was conducted to determine the effect of accounting information systems, internal control and suitability of compensation on fraud prevention at J&T Ekspress Pekanbaru. This research is quantitative research. The population in this study was all J&T Ekspress Pekanbaru employees, totaling 387 people. Sampling used a simple random sampling method with the Slovin formula so that the sample in this study amounted to 80 people. The data in this research uses primary data, with data collection methods using questionnaires. Data analysis in this research uses multiple linear regression analysis with the help of the SPSS 25 program. The results of the research show that the accounting information system, internal control and suitability of compensation have an influence on preventing fraud at J&T Ekspress Pekanbaru.